2000
DOI: 10.1007/bf02708394
|View full text |Cite
|
Sign up to set email alerts
|

Aliphatic amine cured PDMS-epoxy interpenetrating network system for high performance engineering applications—Development and characterization

Abstract: A siliconized epoxy interpenetrating network (IPN) was synthesized from commercially available DGEBA epoxy resin GY250 (Ciba-Geigy, epoxy equivalent = 182-192, viscosity = 9000-12000 cP) and hydroxyl terminated polydimethylsiloxane (PDMS). PDMS and GY250 were thoroughly mixed at 30°C to get the prepolymer. Stoichiometric amounts of PDMS-epoxy prepolymer, γ-aminopropyltriethoxysilane, aliphatic amine curing agent (HY951), and dibutyltindilaurate catalyst, were thoroughly mixed and cast in a mould after evacuati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(12 citation statements)
references
References 10 publications
0
12
0
Order By: Relevance
“…Silicone polymers are widely used as polydimethylsiloxane (PDMS) which is an inorganic polymer and has the properties of being hydrophobic contributed by its non-polar -CH 3 group that gives the coating low surface energy (Ammar et al, 2017). Massive research works have been conducted in the past few years (Sung and Lin, 1997;Velan and Bilal, 2000;Ahmad et al, 2005) to determine the optimum mixing ratio between epoxy resin and PDMS. It has been agreed that the mixing ratio of 90:10 w/w gives the most optimum performance, especially on the research outcome performed by Ananda Kumar together with his research team (Kumar and Narayanan, 2002;Kumar et al, , 2006Duraibabu et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Silicone polymers are widely used as polydimethylsiloxane (PDMS) which is an inorganic polymer and has the properties of being hydrophobic contributed by its non-polar -CH 3 group that gives the coating low surface energy (Ammar et al, 2017). Massive research works have been conducted in the past few years (Sung and Lin, 1997;Velan and Bilal, 2000;Ahmad et al, 2005) to determine the optimum mixing ratio between epoxy resin and PDMS. It has been agreed that the mixing ratio of 90:10 w/w gives the most optimum performance, especially on the research outcome performed by Ananda Kumar together with his research team (Kumar and Narayanan, 2002;Kumar et al, , 2006Duraibabu et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The benzene ring bending vibration absorption peaks of ES-30 are at 1610 cm −1 and 1505 cm −1 , indicating that the crosslinked structure of epoxy resin has been successfully introduced into the siloxane structure. The formation process of the molecular structure can be explained as [27], the first stage is the pretreatment reaction between E51 and LT-550. When the two liquids with different viscosities are mixed uniformly, the epoxy group of E51 epoxy and the amino group of LT-550 undergo a ring-opening reaction.…”
Section: Molecular Structurementioning
confidence: 99%
“…The principle of the reaction is shown in Figure 2. The second stage is the condensation reaction between the hydroxyl group of PDMS and the ethoxy group of hydrolyzed LT-550 under the catalysis of DBTDL to complete the modification of silicone by epoxy [27]. It was found that the viscosity of the system increased during the mixing process.…”
Section: Molecular Structurementioning
confidence: 99%
“…However, the usage was limited due to the porous nature of the coating, hydrophilicity, and less impact strength. 1 Meanwhile, fillerloaded epoxy composite coats yielded an advantage by filling pores. 2 Especially, nanofillers with unique morphology provide homogeneous dispersion thereby restricting the pathways of corrosive species attack.…”
Section: ■ Introductionmentioning
confidence: 99%